Fibroblast activation protein-targeted-4-1BB ligand agonist amplifies effector functions of intratumoral T cells in human cancer - Alfred Zippelius; Petra Herzig; Heinz Läubli; Vaios Karanikas; Gieri Cathomas; Christian Klein; Marta Trüb; Franziska Uhlenbrock; Christina Claus; Martin Thelen; Marina Bacac; Maria Amann; et al. (Journal for ImmunoTherapy of Cancer)
Background The costimulatory receptor 4-1BB (CD137, TNFRSF9) plays an important role in sustaining effective T cell immune responses and is investigated as target for cancer therapy. Systemic 4-1BB directed therapies elicit toxicity or low efficacy, which significantly hampered advancement of 4-1BB-based immunotherapy. Therefore, targeted delivery of 4-1BB agonist to the tumor side is needed for eliciting antitumor efficacy while avoiding systemic toxicity.Methods We analyzed the immunostimulatory properties of a fibroblast activation protein (FAP)-targeted 4-1BB agonist (FAP-4-1BBL) by assessing tumor-infiltrating lymphocytes’ (TIL) activity from patients with non-small cell lung cancer and epithelial ovarian cancer.Results Combination treatment with FAP-4-1BBL and T cell receptor stimulation by either anti-CD3 or T cell bispecific antibodies significantly enhanced TIL activation and effector functions, including T cell proliferation, secretion of proinflammatory cytokines and cytotoxicity. Notably, costimulation with FAP-4-1BBL led to de novo secretion of interleukin (IL)−13. This was associated with cytokine-mediated tumor cell apoptosis, which was partially dependent on IL-13 alpha 1/2 receptors and STAT6 phosphorylation.Conclusions Our study provides mechanistic insights into T cell stimulation induced by FAP-4-1BBL in primary human tumors and supports the investigation of FAP-4-1BBL compound in early clinical trials.